If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -9 = 13 + -3x Reorder the terms: -9 + -1x = 13 + -3x Solving -9 + -1x = 13 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -9 + -1x + 3x = 13 + -3x + 3x Combine like terms: -1x + 3x = 2x -9 + 2x = 13 + -3x + 3x Combine like terms: -3x + 3x = 0 -9 + 2x = 13 + 0 -9 + 2x = 13 Add '9' to each side of the equation. -9 + 9 + 2x = 13 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 13 + 9 2x = 13 + 9 Combine like terms: 13 + 9 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 0.45x+0.6=0.6x | | 4lnx=3 | | (5x+3)=(4x-1) | | (6x)=42 | | -22+5x=-4x+32 | | 9x(-1)-7=x | | -7-5[2x-5(10+6x)]= | | -3-x=-2x+8 | | (-0.75x+6)-(2.5x-1.9)= | | 2(3x+2)=2x+1+x | | 100=v+23 | | 7-3x=-4+13 | | 29z+15z+11z+35z+46z+14z= | | (m-n-1)(m-n+1)= | | 25=5r | | x+x+2=758 | | 42=7t | | 17-x=5+6 | | 5b+4=6b-4 | | 3-6x=4x+0 | | 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 | | (6+3x)=x-18 | | 6n+4=28-11 | | 4w^2+12w+9=1169 | | x^2-6x+9=64 | | y+6x=3 | | 7x+3y-8=4 | | 20w^2-31w+12=0 | | 16a^2-70a+49=0 | | 1x+2=-6 |